Diabetes Foot Ulcer Risk - A Public Health Concern in Rural Pondicherry!! - Bijaya N Naik; Manikandan Srinivasan; Mahendra M Reddy; Srikanta Kanungo; Sonali Sarkar; Sitanshu S Kar (Medsci Publications, 2018)
Background: The risk of diabetes related complications is increas- ing with the increase in number of diabetes in rural population. Diabetes foot ulcer is a preventable complication of diabetes. Objective: To assess the diabetes foot ulcer risk among patients with type II diabetes attending a rural health centre in Pondicher- ry. Materials and Methods: This facility based cross sectional study was conducted among 121 diabetics attending a rural health centre in Pondicherry during the study period. Detailed foot examination including vascular and neurological assessment was done using standard procedure. The risk for diabetes foot ulcer was catego- rised as per risk classification by American Diabetic Association. Results: About 17% of the diabetes patients had risk for develop- ing diabetes foot ulcer. Of the total diabetics with risk for foot ul- cer, 5%, 7.5% and 5% were in category 1, category 2 and category 3 respectively. A significant 39% of the diabetics reported not receiv- ing any health education related to foot care. Conclusion: A significant proportion of diabetics had risk for foot ulcer in the study population. Health education on foot care for all diabetics and close monitoring of foot of diabetics with risk for de- veloping foot ulcer should be included in routine care.